2010 NATO Strategic Concept in the Context of Security Ensuring in Europe - K P Kurylev; D V Kazanchev (Vestnik RUDN. International Relations, 2013)
The analysis of key positions of the Lisbon Strategic concept of the North Atlantic Alliance accepted in 2010 has been made. The authors pay attention to the fact, that the new doctrine of the NATO urged to give the adequate answer to the threats which NATO-countries are faced. Authors believe that the development of the discussion about the European security shows that at present «the Big Europe», which main guarantor of safety is the NATO, isn't ready to involve Russia as the equal partner in the process of construction of one and indivisible, fair system of the European security.